2021
DOI: 10.1186/s12987-021-00251-6
|View full text |Cite
|
Sign up to set email alerts
|

Direction and magnitude of cerebrospinal fluid flow vary substantially across central nervous system diseases

Abstract: Background Several central nervous system diseases are associated with disturbed cerebrospinal fluid (CSF) flow patterns and have typically been characterized in vivo by phase-contrast magnetic resonance imaging (MRI). This technique is, however, limited by its applicability in space and time. Phase-contrast MRI has yet to be compared directly with CSF tracer enhanced imaging, which can be considered gold standard for assessing long-term CSF flow dynamics within the intracranial compartment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 54 publications
1
47
0
Order By: Relevance
“…Estimation of tracer enrichment within ventricles using FreeSurfer software showed that tracer enrichment closely follows the categorical grading of reflux. Phase-contrast MRI supports the net retrograde aqueductal flow of CSF in iNPH ( 17 , 50 , 51 ). Others also reported net retrograde CSF flow within the cerebral aqueduct in patients with communicating hydrocephalus ( 50 , 52 56 ).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Estimation of tracer enrichment within ventricles using FreeSurfer software showed that tracer enrichment closely follows the categorical grading of reflux. Phase-contrast MRI supports the net retrograde aqueductal flow of CSF in iNPH ( 17 , 50 , 51 ). Others also reported net retrograde CSF flow within the cerebral aqueduct in patients with communicating hydrocephalus ( 50 , 52 56 ).…”
Section: Discussionmentioning
confidence: 72%
“…Others also reported net retrograde CSF flow within the cerebral aqueduct in patients with communicating hydrocephalus ( 50 , 52 56 ). On the contrary, other disease categories of CSF disturbance, e.g., idiopathic intracranial hypertension and spontaneous intracranial hypotension or brain cysts, demonstrated no ventricular reflux of tracer ( 17 ). Likewise, individuals without CSF disturbance showed no ventricular tracer reflux ( 17 ), or net retrograde aqueductal flow ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have implicated 1) forced inspiration in humans 12 , 2) cardiac pulsation with some contribution from respiration in humans 37 , and 3) cardiac pulsation in rodents 7 , as major drivers of CSF flow. Recent work by extension has also examined the magnitude, direction, and sensitivity of CSF movement to respiratory performances and locations [14][15][16]45,46 , and more recently, low-frequency oscillations (e.g., vasomotion; ~ <0.1 Hz) 9,47,48 including during sleep 9 . For instance, in a recent study conducted while subjects sleeping in an MRI scanner, Fultz and colleagues 9 demonstrated that CSF flow oscillations during non-rapid eye movement (NREM) sleep were (5.52 dB) larger and slower (0.05 Hz vasomotion) compared to wakefulness (0.25 Hz respiratory), and suggested that increased pulsatile CSF dynamics during sleep may alter the brain's waste clearance due to increased mixing and diffusion 2,49 .…”
mentioning
confidence: 99%